Clinical outcomes of a new hybrid monofocal IOL with extended depth of focus - Baur, Isabella; Khoramnia, Ramin; Weindler, Jan N.; Naujokaitis, Tadas; Poompokawat, Piyanut; Auffarth, Gerd U. (Journal of refractive surgery, 2021)
PURPOSE: - - To evaluate a new extended depth of focus intraocular lens (IOL), the xact Mono-EDOF ME4 (Santen Pharmaceuticals), Conformitè Europëenne-marked as a monofocal IOL, which has four diffractive rings intended to enhance intermediate vision. - - METHODS: - - Results are reported for 47 IOLs implanted in 28 patients who underwent cataract surgery and implantation of the xact Mono-EDOF ME4 IOL in one (9 patients) or both (19 patients) eyes. Postoperative follow-up examinations included visual acuity testing (monocular and binocular; uncorrected distance visual acuity [UDVA], corrected distance visual acuity [CDVA], uncorrected intermediate visual acuity [UIVA], distance-corrected intermediate visual acuity [DCIVA]), defocus curve and contrast sensitivity testing, and dysphotopsia evaluation. - - RESULTS: - - Follow-up at 6 months postoperatively revealed a monocular UDVA of 0.08 ± 0.15 logMAR, binocular UDVA of −0.02 ± 0.09 logMAR, monocular CDVA of −0.07 ± 0.08 logMAR, binocular CDVA of −0.09 ± 0.09 logMAR, monocular UIVA (70 cm) of 0.18 ± 0.16 logMAR, binocular UIVA (70 cm) of 0.09 ± 0.12 logMAR, monocular DCIVA (70 cm) of 0.25 ± 0.14 logMAR, and binocular DCIVA (70 cm) of 0.13 ± 0.11 logMAR. Defocus curve testing demonstrated a functional defocus of 1.25 diopters at 0.20 logMAR for monocular and 1.50 diopters at 0.20 logMAR for binocular testing. The contrast sensitivity corresponded to the age-appropriate normal values. Patients reported low levels of halo and glare. - - CONCLUSIONS: - - The xact Mono-EDOF ME4 IOL showed good functional results for far and intermediate distance visual acuity while inducing a low level of photic phenomena. - - [J Refract Surg. 2021;37(9):601-608.]